Has Covid-19 Pandemic had an Impact on the Productivity of Indonesia Zakat Institutions? - Mimma Maripatul Uula; Nun Maziyyah (SMART Insight, 2023)
This study aims to measure the productivity of zakat institutions in Indonesia using the Malmquist Productivity Index (MPI) method with the research period 2016-2022. The research objects used are 7 zakat institutions in Indonesia. The data of this study comes from the annual financial statements of each institution from the period 2016-2022. The input variables in this study are employee costs, operational costs and total assets. And for the output variable is the collection and distribution of zakat. The results of this study explain that during the period 2016-2022, the productivity level of zakat institutions in Indonesia has a fluctuating trend from year to year. Based on the average TFPCH score, it is concluded that the productivity of zakat institutions shows a decline and technological change has not contributed optimally to the increase in the productivity of zakat institutions in Indonesia. Furthermore, the productivity of Zakat Institutions during the Covid-19 pandemic has a significant influence on the productivity level of LAZ in Indonesia. Then, there are only two LAZs that have increased productivity, namely BAMUIS BNI and YBM PLN. We also apply quadrant analysis to divide zakat institutions based on efficiency and technological changes value.